Methicillin Resistant Staphylococcus Aureus Causing Pyopneumothorax in a Child - Owais, Syeda Sobya; Khan, Abdus Salam; Khan, Ejaz Ahmed (Infectious Diseases Journal of Pakistan, 2023)
Methicillin Resistant Staphylococcus Aureus Causing Pyopneumothorax in a Child Initially described as hospital-acquired , methicillin-resistant Staphylococcus aureus (MRSA) has emerged as a significant community-acquired pathogen as well, causing serious infections, even in children. In the past decade, there has been a substantial increase in its prevalence, attributable to distinctive genotypes that appear to have evolved in the community.1 We describe a previously healthy boy presenting with pyopneumothorax caused by community-acquired MRSA.